EKSPLORASI ASAL USUL DAN MAKNA SIMBOLIK SITUS MEGALITIK BATU GAJAH DI DOLOK PANRIBUAN SIMALUNGUN SUMATERA UTARA DARI PERSPEKTIF TRADISI LISAN - Hasugian, Jalatua Habungaran (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This research on the Batu Gajah Megalithic Site in Dolok Panribuan, Simalungun, North Sumatra aims to explore the origins and symbolic meaning of the site through an oral tradition approach that lives in the local community (Simalungun). Through qualitative methods based on in-depth interviews with key informants, it emerged that apart from historical artifacts, this site also has strong religious, symbolic and social values for the local community.This oral tradition about the origins of the Batu Gajah Site has the nuances of myth and legend, reflecting the relationship between humans, nature and supernatural forces. The research results show that the Batu Gajah Site is an integral symbol of the continuity of local traditions and functions as a link between the past and the present in the context of folklore in Simalungun. This research also emphasizes the importance of preserving oral traditions to understand megalithic heritage and efforts to preserve oral knowledge to maintain the continuity of the community's collective memory.